A HUMANISING ECONOMIC APPROACH ON COMPETITION POLICY OR HOW THE BEHAVIORAL ECONOMICS BLENDS WITH “TRADITIONAL ECONOMICS” - Niminet, Liviana Andreea (Studies and Scientific Researches. Economics Edition, 2015)
Behavioral are crucial for understanding both the consumer’s attitude and firms’ attitude as well as for understanding the market outcomes. The past ten years brought a lot of attention from researchers and policy-makers on the behavioral economics issue. Classical, traditional economic models rely on the assumptions of rationality and ordered preferences. Behavioral economics explores interactions between demand and supply including information framing, the use of heuristics in decision-making and time-inconsistent preferences. The research on behavioral economics has led to an extensive debate about the relative merits of both traditional and behavioral economics. First of all we propose to highlight the advantages and disadvantages of behavioral economics versus traditional economics on a very sensitive issue: the competition policy. Then we address market issues that can be solved by means of behavioral economics afterwards turning out attention to the remedies of behavioral economics and ,last but not least, the United Kingdom successful model on the matter of competition policy.